Stakeholders, eventos corporativos e hospitalidade: estudo de casos múltiplos em bourbon hotéis e resorts - GUIZI, Alan Aparecido (2015)
The 80% increase in corporate travel recorded between 2006 and 2012, indicated by the Economic Index of Corporate Travel - IEVC (ALAGEV,2013) demonstrates the potential of the enterprise mobility market by means of research meetings at the Universidade Anhembi Morumbi (Brazil),has brought to light research that includes business events, which caused the interest of companies related to hospitality. Thus, this study aimed at "noting the effects of hospitality insertion inside Bourbon hotels and their stakeholders in hosting corporate events." The research also pursued the following specific objectives: a) to check whether there is hospitality between the hotel and its stakeholders of corporate events; b) to identify whether the inclusion of hospitality in the relationship between hotel and stakeholders (internal and external) creates an environment of mutual trust that contributes to business improvement; c) to discuss the hospitality in services as a competitiveness factor in hosting corporate events inside the researched hotels. Therefore, the following issue was established: "What are the benefits of the inclusion of Hospitality between Bourbon Hotels and Resorts and its stakeholders when holding corporate events? ". The following proposals were considered; (P1) The hospitality in the relationship between hotel and corporate events of stakeholders contributes to revenue generation, increased flow of customers and attracts new business; (P2) The insertion of hospitality in the relationship with stakeholders, both internal (employers or employees) and external (partner companies or customers) creates an environment of mutual trust, motivating them to carry out actions in both short and long term; (P3) Holding events highlights the infrastructure and hospitality of the hotel-based network services, which are considered as its competitive factors, attracting market demands to book other events in their premises that end up resulting in financial increase. It is an exploratory research, which had its methodology based on literature articles, dissertations, theses, books, texts, online and mass media, with special attention to those dating from the last five years, among other sources. After the development of the theoretical work, the study of multiple case studies was carried out, after the preparation of the protocol suggested by Yin (2010), which previewed the use of semi-structured interviews. Those interviews were transcribed with the elimination of errors and grammatical language vices, and were carried out according to each subject’s availability, as well as technical visits to the chosen hotels. Content analysis was also adopted, according to Bardin (2011), for encoding and theming of interview, reflected in the plan preparation, and also later for interpreting the interviews speech. As study objects, three units of Bourbon Hotels and Resorts were chosen: Bourbon Cataratas Convention & Spa Resort (Foz do Iguaçu, Paraná, Brazil), Bourbon Curitiba Convention Hotel (Curitiba, Parana, Brazil), and Bourbon Atibaia Convention & Spa Resort (Atibaia, São Paulo, Brazil). Eventually, the three propositions analyzedwere taken, since the hospitality of hotel chain and its stakeholders generate competitiveness for the hospitality organization by creating a relationship based on mutual trust, which attracts the possibility of agreements, new events and financial results.